2015
DOI: 10.1002/rcs.1701
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted laparoscopic resection of large retroperitoneal paraganglioma – initial experience from China

Abstract: With the advantages of robotic system, robot-assisted resection of large retroperitoneal PGL is feasible, safe and efficient. The robotic system has the potential to expand surgical treatment modalities for complex PGL. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some reports have indicated that the retroperitoneal approach shortens the surgical duration 32,33 . In addition, reports also exist on the single‐site and robotic surgeries 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Some reports have indicated that the retroperitoneal approach shortens the surgical duration 32,33 . In addition, reports also exist on the single‐site and robotic surgeries 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…For the former, we choose retroperitoneoscopic approaches, while for the latter, tumors were removed using transperitoneoscopic approaches (6,20). In addition, with the rise of robotic surgery by Leonardo Da Vinci, some medical centers have been using this method to break through the limit of tumor resection, which also has a good application prospect (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic surgery for abdominal PGLs has been proved to be as reliable as laparotomy. Some surgeons insist a retro-peritoneal laparoscopic surgery for suprarenal PGLs and a transperitoneal laparoscopic surgery for infrarenal PGLs [40]. However, the anatomic variations, instability haemodynamics during operation, close to major blood vessels, peripheral dense adhesions and hypervascularity of PGLs make laparoscopic resection extremely difficult [41].…”
Section: Discussionmentioning
confidence: 99%